2008
DOI: 10.1007/s10456-008-9093-5
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and amplification of toll-like receptor (TLR) and receptor for advanced glycation end products (RAGE) signaling pathways via high mobility group B1 (HMGB1)

Abstract: Sustained proinflammatory responses in rheumatoid arthritis, atherosclerosis, and diabetic retinopathy, as well as in cancer, are often associated with increased angiogenesis that contributes to tissue disruption and disease progression. High mobility group B1 (HMGB1) has been recognized as a proinflammatory cytokine and more recently, as a proangiogenic factor. HMGB1 can either be passively released from necrotic cells or actively secreted in response to angiogenic and inflammatory signals. HMGB1 itself may s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
409
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(433 citation statements)
references
References 73 publications
18
409
1
5
Order By: Relevance
“…Higher HMGB1 levels have been found in tumors with greater metastatic potential (25). Except for inducing Tim-3 expression in endothelial cells as shown in this study, HMGB1 also up-regulates the expression of Eselectin in endothelial cells (4,25). E-selectin modulates transmigration of tumor cells by enhancing transendothelial permeability and migration of tumor cells (26)(27)(28).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Higher HMGB1 levels have been found in tumors with greater metastatic potential (25). Except for inducing Tim-3 expression in endothelial cells as shown in this study, HMGB1 also up-regulates the expression of Eselectin in endothelial cells (4,25). E-selectin modulates transmigration of tumor cells by enhancing transendothelial permeability and migration of tumor cells (26)(27)(28).…”
Section: Discussionsupporting
confidence: 60%
“…Importantly, endothelial cells also contribute to tumor inflammation and metastasis (1)(2)(3). TLR4 expressed in endothelial cells can be activated by engaging with TLR4 ligands such as LPS or high mobility group box 1 (HMGB1) (4,5). Subsequently, various inflammatory factors are induced in endothelial cells (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…In return, HMGB1 triggers the expression of other proinflammatory cytokines and reinforces this way the proinflammatory process (Andersson et al, 2000;Wang et al, 1999). Endothelial cells express HMGB1, as well as its receptors RAGE, TLR2 and TLR4 and signalling through theses receptors leads to activation of NFkappaB, which can subsequently induce the expression of HMGB1 receptors (van Beijnum et al, 2008) These studies suggest that HMGB1 may be a critical proinflammatory cytokine and may play an important role in the pathogenesis of CAD. Hu et al (2009) has found markedly increased level of serum HMGB1 that correlated with severity of coronary artery stenosis in patients with stable (SAP) and unstable angina pectoris (USAP), especially in SAP patients.…”
Section: Hmgb1 In Positive Feedback Mechanismmentioning
confidence: 94%
“…der Redox-Zustand von HMGB1 der Schl ü ssel zum Verst ä ndnis der gegens ä tzlichen Funktionen sein. [106] . Beim oralen Plattenepithelkarzinom fand sich zudem eine Korrelation von RAGE-und VEGF-Werten [107] .…”
Section: Unempfindlichkeit Gegen ü Ber Wachstumsinhibitorenunclassified